Pharmacological administration of the isoflavone daidzein enhances cell proliferation and reduces high fat diet-induced apoptosis and gliosis in the rat hippocampus. - Rivera-González, Patricia; Pérez-Martín, Margarita; Pavón, Francisco Javier; Serrano, Antonia; Crespillo, Ana; Cifuentes-Rueda, Manuel; López-Ávalos, María Dolores; Mateos-Grondona, Jesús; Vida, Margarita; Fernández-Llebrez, Pedro; Rodriguez-de-Fonseca, Fernando; Suárez-Pérez, Juan (PLOS, 2013)
Soy extracts have been claimed to be neuroprotective against brain insults, an effect related to the estrogenic properties of isoflavones. However, the effects of individual isoflavones on obesity-induced disruption of adult neurogenesis have not yet been analyzed. In the present study we explore the effects of pharmacological administration of daidzein, a main soy isoflavone, in cell proliferation, cell apoptosis and gliosis in the adult hippocampus of animals exposed to a very high-fat diet. Rats made obese after 12-week exposure to a standard or high-fat (HFD, 60%) diets were treated with daidzein (50 mg kg(-1)) for 13 days. Then, plasma levels of metabolites and metabolic hormones, cell proliferation in the subgranular zone of the dentate gyrus (SGZ), and immunohistochemical markers of hippocampal cell apoptosis (caspase-3), gliosis (GFAP and Iba-1), food reward factor FosB and estrogen receptor alpha (ERα) were analyzed. Treatment with daidzein reduced food/caloric intake and body weight gain in obese rats. This was associated with glucose tolerance, low levels of HDL-cholesterol, insulin, adiponectin and testosterone, and high levels of leptin and 17β-estradiol. Daidzein increased the number of phospho-histone H3 and 5-bromo-2-deoxyuridine (BrdU)-ir cells detected in the SGZ of standard diet and HFD-fed rats. Daidzein reversed the HFD-associated enhanced immunohistochemical expression of caspase-3, FosB, GFAP, Iba-1 and ERα in the hippocampus, being more prominent in the dentate gyrus. These results suggest that pharmacological treatment with isoflavones regulates metabolic alterations associated with enhancement of cell proliferation and reduction of apoptosis and gliosis in response to high-fat diet.
Keywords: Factores de transcripción; Fitoestrógenos; Estradiol; Síndrome metabólico; Obesidad; Neurobiología del desarrollo; Estrogen-receptor-alpha